Plan De Marketing Turístico Para El Atractivo Natural La Cascada La Banda Y La Gastronomía Típica De Gonzanamá, Cabecera Cantonal De Gonzanamá De La Provincia De Loja - Jumbo Jumbo, Angel Miguel (2016)
Loja Province located south of the country geographically divided between 16 cantons, is a province rich in culture becoming known as the Castilian city of Ecuador, geography found within a variety of climates and environments that make for an interesting place development of tourism that it is not yet fully exploited by all and sundry. It is here in this province where the Canton Gonzanamá located in a beautiful and large area southwest of Canton Loja on the slopes of Colambo , the name of the canton comprises two Quichua - avocado words Gonza = surname of the chief of the tribe of the anamáes ; and anama = estimated land has an urban and four rural parish , the September 27, 1943 the Legislative Decree No. 928, by which the county is created Gonzanamá approved. The decree was signed by Dr. Carlos Arroyo del Río, President of the time. Gonzanamá urban parish is a place that has a mild climate where agriculture and livestock likewise has a variety of tourist attractions and a varied gastronomy of this region some of them unknown or little interest from the developed population This is why I thought it appropriate to propose the following thesis topic “Tourism Marketing Plan for natural attractive waterfall band and cuisine of Gonzanamá, cantonal Gonzanamá header of the province of Loja ." The main objective was to develop a tourism marketing plan for the waterfall Band and Gonzanamá cuisine of the province of Loja in order to publicize the tourism potential of this place, with three specific objectives are. Conduct an assessment of the current status of the band and cascade the cuisine in Gonzanamá which was fulfilled using the analytical method and techniques of direct observation, interviews and surveys of the economically active population, and tools used as tokens MINTUR description and nesting. Similarly, as the second specific objective was proposed to design the proposal to promote the waterfall Band and local cuisine using the deductive method yielded accurate conclusions from general aspects and thus propose any appropriate advertising solutions . And last socialize marketing plan proposal by the descriptive method and through exposure to the municipal authorities of GAD Gonzanamá involved in the tourism aspect thereby complying with the objectives. After analyzing the data collected through these tools , methods and results including were obtained : the socialization of the proposal with the development of each of the objectives comprising : an analysis of the current situation of urban parish Gonzanamá in their tourist, economic and social infrastructure, the state of the roads and tourist activities so as to develop social needing further attention , the development of a logo which printed anger in a model of t and a model design handles with the side of the waterfall , developing a training plan and a brochure with description of typical dishes most representative of Gonzanamá . As conclusions that this natural attraction and the cuisine lacks infrastructure and adequate promotion which is a limiting factor for its people to develop tourism , having the possibility of implementing a generating alternative economic resources as currently their main source of income is agriculture and livestock. As recommendations to the authorities , residents and public and private entities Canton Gonzanamá give the necessary attention and promotion in the tourism sector in order to allocate among this place in an important seat . The research work presented here is the responsibility of the municipal authorities of Gonzanamá GAD , for the implementation of this marketing plan as they see necessary.